2012
DOI: 10.1017/s1355617712000410
|View full text |Cite
|
Sign up to set email alerts
|

Alerting Network Dysfunction in Early Multiple Sclerosis

Abstract: The objective of this study is to assess attention in recently diagnosed relapsing-remitting multiple sclerosis patients. Twenty-seven patients with early multiple sclerosis and low clinical disability scores (EDSS<2) and 27 sex-, age-, and education-matched healthy controls underwent attention assessment using the Attentional Network Test, a computerized task designed to measure efficiency independently in 3 attentional networks (Alerting, Orienting and Executive Control). MS patients had significantly less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
24
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
5
24
1
Order By: Relevance
“…No significant differences in specific network effects have been found when small samples of patients and controls are compared (e.g., N = 11: Ishigami et al, 2013;N = 12: Omisade et al, 2012), probably due to these studies' insufficient statistical power. However, when larger samples were examined, both Urbanek et al (2010) and Crivelli et al (2012) reported deficits in patients' alerting network, whereas Wojtowicz et al (2013) found impaired performance on the executive control network.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…No significant differences in specific network effects have been found when small samples of patients and controls are compared (e.g., N = 11: Ishigami et al, 2013;N = 12: Omisade et al, 2012), probably due to these studies' insufficient statistical power. However, when larger samples were examined, both Urbanek et al (2010) and Crivelli et al (2012) reported deficits in patients' alerting network, whereas Wojtowicz et al (2013) found impaired performance on the executive control network.…”
mentioning
confidence: 90%
“…Several studies have compared MS patients and controls on the attention networks comprising Posner's model (Crivelli et al, 2012;Ishigami, Fisk, Wojtowicz, & Klein, 2013;Omisade et al, 2012;Urbanek et al, 2010;Wojtowicz, Omisade, & Fisk, 2013). No significant differences in specific network effects have been found when small samples of patients and controls are compared (e.g., N = 11: Ishigami et al, 2013;N = 12: Omisade et al, 2012), probably due to these studies' insufficient statistical power.…”
mentioning
confidence: 99%
See 3 more Smart Citations